(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: One of the most relevant problems in the Republic of Uzbekistan today in this review is the importance of healthy family planning, that is, maintaining the interval between births, in reducing maternal and child mortality, and the correct choice of the type of contraception for each woman and an individual approach to it.